Strategies for stimulating poverty-alleviating growth in the rural nonfarm economy in developing countries - Haggblade, Steven; Hazell, Peter B. R.; Reardon, Thomas (World Bank, 2002)
The rural nonfarm economy (RNFE) accounts for roughly 25 percent of full-time rural employment and 35-40 percent of rural incomes across the developing world. This diverse collection of seasonal trading, household-based and large-scale agroprocessing, manufacturing and service activities plays a crucial role in sustaining rural populations, inservicing a growing and modern agriculture, and in supplying local consumer goods and services. In areas where landlessness prevails, rural nonfarm activity offers important economic alternatives for the rural poor....Three key groups currently intervene in the rural nonfarm economy: large private enterprises, non-profit promotional agencies and governments. Large modern corporations take investment, procurement and marketing decisions that powerfully shape opportunities in the rural nonfarm economy throughout much of the Third World...." The authors put forth three basic principles for policy makers who want to ensure equitable growth of the RNFE: (1) Identify key engines of regional growth; (2) Focus on subsector-specific supply chains; and (3) Build flexible institutional coalitions. They conclude that a prosperous rural nonfarm economy can contribute to both aggregate economic growth and improved welfare of the rural poor. -- from Executive Summary.